Bourdonnements des insectes et musique de David : image sonore de l’Éthiopie chez le père franciscain Remedius Prutký (1752) - Anne Damon-Guillot (Afriques)
This article analyses the accoustic images of Ethiopia given by the Franciscan father Remedius Prutky in his travelogue Itinerarium, written in the mid-17th c., a text recently edited and translated. A sensory-oriented reading of this text is possible by paying attention to the way the catholic missionary "hears" orthodox Christian Ethiopia. This yields a new, sensory understanding of the perception of otherness. Prutky, in masterful rhetoric, ascribes high symbolical value, very often biblical, to the sounds he heard in Ethiopia. His aim was partisan: to give audible form to the heresy of the Ethiopian Christianity. Nonetheless, his description of Ethiopian musical practices, especially in religious contexts, are of great interest for historical musicology.